NEW SPACES TO CONSIDER THE VICTIM AND HIS INTERESTS IN SPANISH CRIMINAL PROCEDURE - Belén Hernández Moura (Revista Eletrônica de Direito Processual, 2019)
The present study analyzes the recent changes in the traditional concept of criminal procedure, considering the trend of an increasing concern with the victim´s wellness. Consequently, it is necessary to analyze the quality of the Justice system, in order to confirm whether the criminal process is granting protection, security as well as the minimum conditions to provide answers to the legitimate expectations of participation, protection, reparation and assistance. The proactive victimology stablishes as its objectives the achievement of the victim´s interests, as well as measures the system´s reaction to those expectations.